The Funerary Ensemble of Nairis in the Hermitage Museum - Meffre, R. (Zeitschrift für ägyptische Sprache und Altertumskunde, 2016)
Publication of a funerary ensemble brought back from Egypt in 1827 by Anastasios Averoff and now kept in the Hermitage museum, Saint Petersburg. It comprises an outer coffin and a cartonnage pertaining to a woman named Nairis, who lived in the Theban area at the end of the Libyan Period. She may be identified with the mother of a maid, known through her coffin and her funerary stele, both items dated to the 25 th Dynasty.